2022
DOI: 10.4028/p-1i2y29
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Waste Materials for Eco-Friendly Building Ceilings: An Overview

Abstract: The pioneers of the industrial revolution, and their successors, left the world’s ecosystem in a devastating state. Global warming became the consequence of activities in the industry that led to climate change, the depletion of the ozone layer, and pollution of the ecosystem. For decades now, concerned researchers have been frantically investigating methods and procedures that can help conserve the ecosystem's left to attain sustainability. The construction industry also poses its challenge as novel solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…One of the problems arising during sorting of the remains of buildings after destruction as a result of military operations in Ukraine is the presence of elements destroyed by fire, hazardous chemicals and biological waste in case of deaths in the building. However, in such crisis situations as war, there are likely to be risks of facing environmental degradation and exacerbation of problems associated with the accumulation of unprocessed waste [1]. There are some particularities of the recycling of construction materials primarily caused by the nature of materials and their physical and chemical properties, which contributes to the development of new recycling methods for each fraction of waste and improvement of the efficiency of existing recycling systems [2].…”
Section: Related Workmentioning
confidence: 99%
“…One of the problems arising during sorting of the remains of buildings after destruction as a result of military operations in Ukraine is the presence of elements destroyed by fire, hazardous chemicals and biological waste in case of deaths in the building. However, in such crisis situations as war, there are likely to be risks of facing environmental degradation and exacerbation of problems associated with the accumulation of unprocessed waste [1]. There are some particularities of the recycling of construction materials primarily caused by the nature of materials and their physical and chemical properties, which contributes to the development of new recycling methods for each fraction of waste and improvement of the efficiency of existing recycling systems [2].…”
Section: Related Workmentioning
confidence: 99%
“…It was identified that the thermal conductivity of the cement paste drastically decreased when adding 4% cellulose fibers. Furthermore, Dirisu et al [105] conducted a study investigating the thermal conductivity of various ceiling tiles using waste materials. The study results showed that the ceiling tiles made from pine fiber had the lowest thermal conductivity value among all the materials tested.…”
Section: Energy Performancementioning
confidence: 99%